The differential diagnosis of localised amelanotic limbal lesions: a review of 162 consecutive excisions. Issue 3 (13th September 2010) - Rudkin, Adam K; Dodd, Tom; Muecke, James S
Abstract : Aims: To report the distribution of histopathological diagnoses in patients who underwent excision of localised limbal lesions that were clinically suspected to be squamous neoplasia (intra-epithelial neoplasia or squamous cell carcinoma). Methods: 162 consecutive patients of a single ocular oncologist underwent an excisional biopsy between 1998 and 2009 for suspected squamous neoplasia. Histopathological reports were retrospectively reviewed. Results: The population comprised 122 males and 40 females. The mean age was 63.4±15.8 (range: 27–90). 138 (85.2%) lesions were identified as intraepithelial neoplasia (CIN), of which 34 (21.0%) were CIN I, 32 (19.8%) were CIN II and 72 (44.4%) were CIN III or squamous cell carcinoma in situ. In seven (4.3%) cases, the lesion was invasive squamous cell carcinoma. In two (1.2%) cases, the lesion was amelanotic malignant melanoma. In 16 (9.9%) cases, histopathology revealed a benign entity including lesions described as squamous papilloma, solar elastosis and epithelial hyperplasia, keratosis or reactive atypia. Conclusions: In this population, for an experienced ocular oncologist, the misdiagnosis of localised limbal squamous neoplasia occurred in 10.5% of cases, with 5.5% of cases being malignant. This study highlights the importance of acquiring a clinical diagnosis before administering a topical chemotherapeutic agent.